A direct proof of a theorem of K. Baron - Gebert, Holger (Annales Mathematicae Silesianae, 1995)
In his work on the Gołąb-Schinzel equation, K. Baron shows a theorem concerning continuous complex-valued solutions, defined on the complex plane. In this note, we will give a direct proof of this theorem, which does not use the form of the general solution of the Gołąb-Schinzel equation.